Temperature dependences of the kinetic coefficients of a bismuth telluride microwave prepared by a novel technique - Meglei, Dragoş (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2017)
An improved technique for preparing glass-insulated microwires of highly volatile materials has been proposed, developed, and tested; owing to the isolation of the material from the environment, this technique provides the formation of a microwire with physical parameters corresponding to those of the starting material. The microwire preparation technique has been tested using a bismuth telluride (Bi2Te3) alloy. The thermopower and conductivity of the Bi2Te3 microwire have been measure in a temperature range of 10–300 K. The derived data for Bi2Te3 in the form of a microwire and a bulk crystal have been compared.